Mechanical stability: a construction principle for cells - Wolff, Lars; Kroy, Klaus (Diffusion Fundamentals, 2009)
The glassy wormlike chain model is a highly successful phenomenological model recently introduced to describe anomalously slow subdiffusive dynamics in biopolymer networks and living cells. Here we extend this model by proposing a generic scheme how to include nonlinear plastic effects by introducing the possibility of force-dependent opening and closing of internal bonds. Further, we discuss physiological implications of this bond kinetics. Stability arguments lead us to the postulation of a “physiological sheet” in the parameter space. This sheet defines the set of parameters characterizing cells which are flexible enough to perform biological tasks while still being able to bear external perturbations characteristic of their surroundings and their internally generated prestress without damage. At the end of this contribution, we speculate about the connection between prestress and cell stiffness and about the mechanism by which the cell adapts to its mechanical environment.